Enhancing Students' Critical Thinking and Creativity through Local Wisdom-Based Literacy Projects Incorporating Tri Nga and Tri N - Krishantari, Dhian Yulia (Universitas Pendidikan Ganesha, 2025)
The low levels of critical reasoning and creativity among primary school students remain a significant challenge in strengthening the Pancasila student profile. The absence of culturally-based learning models that effectively enhance these competencies also hinders the implementation of meaningful education. This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project based on Tri Nga (Ngerti, Ngrasa, Nglakoni) integrated with Tri N (Niteni, Nirokke, Nambahi) through the My Book program, and to evaluate its contribution to improving students' critical reasoning and creative dimensions. This research employed a descriptive qualitative method involving 33 students and 2 teachers. Data were collected through observation, attitude observation rubrics, interviews, and documentation. The data were analyzed using Miles and Huberman’s interactive analysis model, comprising data reduction, data display, and conclusion drawing/verification. The findings indicate that the project implementation enhanced students' ability to formulate questions by 36.36%, express opinions by 54.54%, and reflect by 54.54% in the critical reasoning dimension. Meanwhile, the creativity dimension improved by 34.85%, particularly in students’ ability to innovate, develop ideas, and articulate their thoughts to others. In conclusion, the My Book program based on Tri Nga and Tri N effectively develops primary school students' critical reasoning and creativity. This implies the potential of culturally-based programs as alternative models for character education in primary schools.